The effects of competition and achievement orientedness on helping behaviour. - Lee, Augustine Tian Rong. (2010)
This study explored the effects of competition and achievement orientedness on helping behaviour. Three hypotheses were tested. 1) Participants in competitive and self-competitive conditions would help less as compared to participants in a non-competitive condition. 2) Higher achievement orientedness would lead to a decrease in helping behaviour. 3) Achievement orientedness would affect participants’ helping behaviour but only in the competitive condition and not in the self-competitive and non-competitive conditions. One hundred and sixteen participants from Nanyang Technological University of Singapore were randomly assigned to three different conditions (competitive, non-competitive and selfcompetitive) to see if they would help a confederate in the middle of a game. Results of the study supported the third hypothesis but not the first and second hypotheses.